Role of β-1, 3-galactosyltransferase 2 in trigeminal neuronal sensitization induced by peripheral inflammation. (4th May 2017) - Lv, Yiheng; Ren, Lili; Fu, Yunjie; Huang, Keqiang; Bi, Jing
Highlights: B3galt2 gene was expressed in trigeminal ganglion. Dental pulp inflammation induced B3galt2 expression in trigeminal ganglion. Dental pulp inflammation increases TLR4 and NFκB level in trigeminal ganglion. LPS treatment upregulates B3galt2 and TLR4/NFκB in trigeminal ganglion neurons. B3galt2 gene knockdown may partially block the effect of LPS on TLR4/NFκB signaling in trigeminal ganglion neurons. Abstract: Glycosyltransferases are enzymes that catalyze the formation of a variety of glycoconjugates. Glycoconjugates play important roles in the nervous system. β-1, 3-Galactosyltransferase 2 (B3galt2) belongs to the family of β-1, 3-galactosyltransferase, which is one of the major types of glycosyltransferases. Dental pulp inflammation may cause neurophysiological alterations in the trigeminal ganglion (TG), and serve as a good model for investigating the peripheral inflammation and trigeminal neuronal sensitization. In the present study, we investigated the expression of B3galt2 in neuroinflammation using the dental pulp inflammatory model induced by lipopolysaccharide in rat. The expression of B3galt2 gene and protein were determined by reverse transcription PCR, immunohistochemistry and western blot analysis. ELISA assays were used to measure the levels of cytokines in the TG neurons. Toll-like receptor 4 (TLR4) and nuclear factor-κB (NFκB) were evaluated by immunohistochemistry and western blotting. Our results demonstrated that B3galt2 was expressed in the TG, and dental pulp inflammation up-regulated B3galt2 expression in the TG. B3galt2 gene knockdown reduced the secretion of TNFα and IL-6 in the TG neurons. The expression of TLR4 and NFκB in the TG was activated during the inflammation, but B3galt2 gene knockdown inhibited the expression of TLR4 and NFκB. These observations indicated that dental pulp inflammation could induce B3galt2 expression in TG, and that B3galt2 might play a regulatory role in TG neuronal sensitization. These findings suggest that B3galt2 may play an important role in trigeminal neuronal sensitization induced by peripheral inflammation via mediating TLR4/NFκB signaling pathway.